Kaposiform hemangioendothelioma: A facial exophytic presentation - Sanaa ElMrini; Sami Elhamid; Bahaa Razem; Ayoub Khoaja; Meriem Regragui; Faiçal Slimani (Elsevier, 2021)
Kaposiform Hemangioendithelioma (KHE) is a rare, locally aggressive endothelial derived tumor of childhood, often associated with high morbidity and mortality. Whereas common localisation of presentation is represented by skin of the extremities with deep tissue invasion, we present a unique case of a facial exophytic KHE of a 5-year-old female, with no clinical nor radiological signs of deep tissue invasion, showing no signs of complication and treated with surgical excision.